(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
Global citizens are constantly immersed in issues like hydraulic fracturing or "hydrofracturing" that rely upon scientific knowledge and the ability to negotiate multiple forms of evidence and reasoning to make informed decisions. Historically, Environmental Education and Science Education have been well positioned to provide learning experiences that support the development of important skills like Discourse that are requisite for full participation in our worldwide community. In this article, we explore the confluence of environmental education, science education, and the emergence of an empirical model for socio-scientific Issues (SSI) based teaching and learning. While environmental education and science education have distinct differences, there are significant overlaps in content and process. The emergence of SSI from the field of science education presents opportunities to drive environmental education, and a new framework for guiding SSI based teaching and learning can be useful in terms of informing focus, structure and processes for teaching through issues. Using hydrofracturing as a sample issue, we demonstrate how this recently developed SSI framework can be applied to create learning environments that support development of critical Discourse practices and further the goals of science and environmental education. The core aspects of the framework are 1) design elements, 2) learner experiences, and 3) teacher attributes. We elaborate each of these aspects and demonstrate how to reposition science content and the roles of students and teachers to engage in the issue of hydrofracturing. The SSI framework also highlights the importance of a safe classroom community and an awareness of the broader geo-political context when practicing SSI based teaching and learning. This work provides a theoretical and practical basis to drive the fields of science and environmental education towards research and teaching that promote engaged global citizenship and social justice.